2010
DOI: 10.1177/0022034510377094
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Sensitizes P2X3 in Nociceptive Trigeminal Neurons

Abstract: α,β-methylene adenosine 5'-triphosphate (ATP), α,β-meATP; neurokinin-1, NK-1; single-cell reverse-transcription polymerase chain-reaction, single-cell RT-PCR; [Sar(9),Met(O(2))(11)]-substance P, Sar-substance P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…It is possible that changes in P2X3 function under pathological conditions are more complex than simple upregulation or downregulation of expression at the protein level. Understanding the regulatory mechanisms of P2X3 activity is critical in elucidating its function in pain, and the modulation of P2X3 currents by intracellular pathways has recently gained attention (Giniatullin et al, 2003;Wang et al, 2007;Park et al, 2010). We previously reported that depletion of the plasma membrane-specific phospholipid phosphatidilinositol-4,5-bisphosphate (PIP 2 ) decreases P2X3 activity (Mo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that changes in P2X3 function under pathological conditions are more complex than simple upregulation or downregulation of expression at the protein level. Understanding the regulatory mechanisms of P2X3 activity is critical in elucidating its function in pain, and the modulation of P2X3 currents by intracellular pathways has recently gained attention (Giniatullin et al, 2003;Wang et al, 2007;Park et al, 2010). We previously reported that depletion of the plasma membrane-specific phospholipid phosphatidilinositol-4,5-bisphosphate (PIP 2 ) decreases P2X3 activity (Mo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, under PTSD‐like stress conditions, substances are released from various sources that often act synergistically to cause sensitization of afferent nerves to mechanical stimuli . Secondly, P2X3 can interact with other receptors or mediators, which sensitizes other DRG neurons including capsaicin, 5‐hydroxytryptamine, bradykinin, and calcitonin gene related peptide. In addition, TRPV1 channels are activated and sensitized by ATP released during distension; this is especially prevalent in pathological stress states .…”
Section: Discussionmentioning
confidence: 99%
“…This observation prompted a possibility that both opioid-induced stimulation and inhibition of P2X This, seemingly paradoxical, conclusion is in agreement with data on the regulation of P2X 3 receptors by other metabotropic pathways. For example, activation of P2Y 2 receptors inhibits P2X 3 via PTX-sensitive G i /G o linked to PLC, whereas bradykinin and substance P receptors coupled to PTX-insensitive G q proteins stimulate P2X 3 currents through PLC/PIP 2 /DAG/PKC cascade [38][39][40]. Assuming that similar pathways are used by MORs, one could expect that PKC is involved in the stimulatory action of MORs on P3X 3 receptors as well.…”
Section: Dual Effect Of Opioids On P2x 3 Receptorsmentioning
confidence: 99%